Nitric Oxide Functions as a Downstream Signal for Melatonin-Induced Cold Tolerance in Cucumber Seedlings - Feng, Yiqing; Fu, Xin; Han, Lujie; Xu, Chenxiao; Liu, Chaoyue; Bi, Huangai; Ai, Xizhen (Frontiers in Plant Science, 2021)
Melatonin (MT) and Nitric oxide (NO) are two multifunctional signal molecules and participate in the response of plants to abiotic stresses. However, how the synergy of MT and NO in response to chilling of plants is still unclear. In this study, we found that the endogenous MT accumulation under chilling stress was positively correlated with chilling tolerance in cucumber seedlings of different varieties. The data presented here also provide evidences that endogenous NO was involved in the response to chilling stress. 100 μM MT significantly increased the NR activity and relative mRNA expression of NR, which in turn elevated endogenous NO accumulation in cucumber seedlings. However, 75 μM SNP showed no significant effect on the relative mRNA expression of TDC, T5H, SNAT and ASMT, as well as endogenous MT levels. Both MT and SNP notably alleviated chilling damage which as evidenced by lower electrolyte leakage (EL), MDA and reactive oxygen species (ROS) accumulation by activating antioxidant system. MT and SNP also improved the CO2 assimilation, which mainly attributed to an increase in activity and gene expression of photosynthetic enzymes. Of note, MT and SNP simultaneously induced photoprotection for both photosystem II (PSII), and photosystem I (PSI) in cucumber seedlings, by activating the D1 protein repair pathway and ferredoxin-mediated NADP+ photoreduction respectively. Additionally, the chilling response genes (ICE, CBF1, and COR) were obviously upregulated by exogenous MT and SNP. 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3- oxide (cPTIO, a specific scavenger of NO) suppressed MT-induced chilling tolerance, whereas, p-Chlorophenylalanine (p-CPA, MT synthesis inhibitor) did not affect NO-induced chilling tolerance. Thus, novel results suggest that NO acting as a downstream signal is involved in the MT-induced plant tolerance to chilling stress.